Penguatan Kapasitas Peternak Cerdas Iklim melalui Pelatihan Strategi Pemasaran Produk Peternakan Pada CV. Muda Bakti Barokah Farm: Capacity Building for Climate-Smart Farmers Through Training on Marketing Strategies for Livestock Products at CV. Muda Bakti Barokah Farm - Azhary Noersidiq; Fahrullah Fahrullah; Eka Nurminda Dewi Mandalika (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This study aims to enhance farmers’ capacity to cope with the impacts of climate change through training on marketing strategies for livestock products at CV. Muda Bakti Barokah (MBB Farm) in Lelong Village, Central Lombok. The livestock sector plays a crucial role in food security but is vulnerable to climate change, which affects both production and farmers’ incomes. Therefore, capacity building is needed not only in technical aspects of livestock production but also in marketing skills and business management. The method employed was a participatory and applied approach involving 10 participants. The activity was carried out through the stages of survey, socialization, technical training, mentoring, and evaluation. The material covered included marketing strategies, pricing, market segmentation, and the use of digital media. The results of the activity showed a significant increase in participants’ understanding, from 20% on the pre-test to 90% on the post-test. Additionally, the use of social media proved effective in expanding market reach and brand awareness. Another impact was a 14% increase in average sales of livestock products within one month of the activity. All participants responded positively to the training. Thus, this marketing strategy training was effective in enhancing farmers’ capacity to become more adaptive, innovative, and sustainable in addressing the challenges of climate change. This initiative is expected to serve as a model for farmer capacity building to enhance the competitiveness of livestock businesses in the digital age.